Certification of General Educational Institutions as A Type of Quality Monitoring of Basic Educational Programs - Mirkhayitova Sokhiba Ibragimovna; Bakhtiyor Umidovich Aminov; Komilova Sevinch Akmaljon Qizi (Peerian Journals Publishing, 2023)
The quality of education is crucial for the successful development of any country. In developed countries, the intellectual potential determined by the quality of education is becoming an important factor in the well-being of society.
Keywords: quality of education; school education; monitoring